Rapid sensitive validated UPLCâMS method for determination of venlafaxine and its metabolite in rat plasma: Application to pharmacokinetic study - Sunil Kumar Dubey; R.N. Saha; Hemanth Jangala; S. Pasha (Elsevier, 2013)
A new ultra-performance liquid chromatographyâelectrospray ionization mass spectrometry (UPLCâMS/ESI) method for simultaneous determination of venlafaxine (VEN) and its metabolite O-desmethylvenlafaxine (ODV) in rat plasma has been developed and validated using Venlafaxine d6 as the internal standard. The compounds and internal standard were extracted from plasma by solid phase extraction. The UPLC separation of the analytes was performed on ACQUITY UPLCÂ® BEH Shield RP18 (1.7Â Âµm, 100Â mmÃ2.1Â mm) column, using isocratic elution with mobile phase constituted of water (containing 2Â mM ammonium acetate): acetonitrile (20:80, v/v) at a flow rate of 0.3Â mL/min. All of the analytes were eluted within 1.5Â min. The compounds were ionized in the electrospray ionization (ESI) ion source of the mass spectrometer, operating in multiple reaction monitoring (MRM) and positive ion mode. The precursor to product ion transitions monitored for VEN, ODV and Venlafaxine d6 were m/z 278.3â121.08, 264.2â107.1 and 284.4â121.0, respectively. The developed and validated method was used for the pharmacokinetic study of VEN in rats. Keywords: Venlafaxine, O-desmethylvenlafaxine, Metabolite, UPLCâMS/ES